2010
DOI: 10.1007/s12032-010-9681-2
|View full text |Cite
|
Sign up to set email alerts
|

EBV-LMP1-targeted DNAzyme restrains nasopharyngeal carcinoma growth in a mouse C666-1 xenograft model

Abstract: Epstein-Barr virus (EBV)-encoded latent membrane protein 1 (LMP1) has been demonstrated to be linked to the pathogenesis of nasopharyngeal carcinoma (NPC), one of the most common cancers in southeast Asia as well as in the areas of southern China. RNA-cleaving DNAzymes are catalytic nucleic acids that bind and cleave a target RNA and have been increasingly used to inhibit gene expression. In this study, we aimed to explore the effects of down-regulation of LMP1 by DNAzymes on the NPC growth using a mouse xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…[8][9][10][11][12] To date, most NPC xenograft studies have involved the growth of a mass of tumor cells, often subcutaneously, that do not recapitulate human disease because they remain discrete and encapsulated. [8][9][10] In comparison, clinically advanced NPC is characterized by aggressive invasion with erosion and remodeling of facial and skull base cranial bones 13 as well as distant metastasis to solid organs, most commonly bone, lung, and liver. 14,15 To more accurately replicate advanced human disease, we have developed an orthotopic mouse xenograft model of NPC by inserting luciferasetagged tumor cells into the nasopharyngeal region and then following patterns of growth and metastasis over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] To date, most NPC xenograft studies have involved the growth of a mass of tumor cells, often subcutaneously, that do not recapitulate human disease because they remain discrete and encapsulated. [8][9][10] In comparison, clinically advanced NPC is characterized by aggressive invasion with erosion and remodeling of facial and skull base cranial bones 13 as well as distant metastasis to solid organs, most commonly bone, lung, and liver. 14,15 To more accurately replicate advanced human disease, we have developed an orthotopic mouse xenograft model of NPC by inserting luciferasetagged tumor cells into the nasopharyngeal region and then following patterns of growth and metastasis over time.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the information we have about NPC has been derived from studies of well-characterized cell lines in vitro 7 and in vivo using immunocompromised mice. 8-12 To date, most NPC xenograft studies have involved the growth of a mass of tumor cells, often subcutaneously, that do not recapitulate human disease because they remain discrete and encapsulated. 8-10 In comparison, clinically advanced NPC is characterized by aggressive invasion with erosion and remodeling of facial and skull base cranial bones 13 as well as distant metastasis to solid organs, most commonly bone, lung, and liver.…”
Section: Introductionmentioning
confidence: 99%
“…ENV [55][56][57] TAT, TAT-REV [58][59][60][61] TAR [62] GAG, NEF [63] HIV-1 Integrase [64] Vpr [65] Hepatitis B X [66,67] S, C [68,69] DR1 and PA regions of pre-genomic RNA [70] Hepatitis C Core [19,71,72] NS3 [73,74] NS5B [19] IRES [17] Influenza A PB2 [75,76] M1 [77] Influenza B BM2 [21] Respiratory syncytial virus (RSV) N [15,78] Severe acute respiratory syndrome coronavirus (SARS-CoV) 5'-Untranslated region of a highly conserved fragment of SARS genome [79] Epstein-Barr virus LMP1 [80][81][82][83][84][85] Human papilloma virus type 16 E6/E7 [48] Japanese encephalitis virus 3'-Non-coding regions of RNA genome [16] Bacteria Ampicillin-resistant bacteria TEM1, TEM3 b-Lactamase [14] Methicillin-resistant Staphylococcus aureus blaR1 [86] MecR1 [87] Mycobacterium tuberculosis…”
Section: Virusesmentioning
confidence: 99%
“…Another Dz Dz509 targeting the same LMP1 RNA was identified for potential therapeutic application for treatment of NPC [85]. Dz509 showed high activity for inhibition of LMP1 expression as compared to a control mutant Dz mutDz509.…”
Section: Oncovirusesmentioning
confidence: 99%
“…Previously, a 33-mer oligonucleotide LMP1-targeted DNAzyme containing three phosphorothioate linkages at its 5’ and 3’ ends was developed to specifically target LMP1 mRNA [ 11 ]. Down-regulation of LMP1 expression using this LMP1-targeted DNAzyme was found to inhibit the growth of NPC cells both in vivo and in vitro by suppressing cell proliferation and inducing apoptosis [ 2 , 12 ]. Moreover, in a recent study, LMP1-targeted DNAzyme was found to enhance the radiosensitivity of LMP1-positive NPC cells by inhibiting telomerase activity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%